Production of natural astaxanthin by Phaffia rhodozyma and its potential application in textile dyeing - Mussagy, Cassamo U.; Silva, Pedro G.P.; Amantino, Camila F. [UNESP]; Burkert, Janaina F.M.; Primo, Fernando L. [UNESP]; Pessoa, Adalberto; Santos-Ebinuma, Valeria C. [UNESP] (Elsevier, 2022)
Microbial astaxanthin are preferred over the synthetic equivalent, not only to impart color in a wide variety of products but also to provide bioactive antioxidants nutrients to human health. The yeast Phaffia rhodozyma is considered as one of the most important natural sources of astaxanthin. The present research work was designed to enhance the biosynthesis of astaxanthin by using synthetic substrates and moving from orbital shaker to 4 L stirred tank bioreactor (STB). Moreover, it was also evaluated the potential of astaxanthin-rich extracts in dyeing textile fabrics. Under optimal conditions in STB [carbon source (glucose/xylose) and aeration rate (1 vvm) with constant light irradiation], the process production achieved a 503.66 μg/gDCW (+ 48.99%) of astaxanthin compared to the orbital shakers (256.88 μg/gDCW). The in vitro antioxidant activity and potential cytotoxicity assessment of astaxanthin-rich extracts was evaluated, indicating the potential of astaxanthin to be used as a natural dyeing agent for textiles, envisioning the replacement of synthetic colorants by natural counterpart.
Keywords: Antioxidant; Carotenoids; Submerged culture; Textile matrix; Yeast